Analysis Of Factors In Tenders For Procurement Of Construction Goods/Services Using The E-Catalogue System - Krisna Rendi Awalludin; I Nyoman Dita Pahang Putra (Journal of Civil Engineering and Planning (JCEP), 2024)
The government is updating regulations for procuring goods and services by introducing an e-catalogue system in the auction/tender process. Construction companies need to study the factors in tenders for the Procurement of construction goods/services using the e-catalogue system to ensure that the tender process using the e-catalogue system runs well and optimally. This research aims to analyze the factors in tenders for the Procurement of construction goods/services using the e-catalogue system. The method used was distributing questionnaires to small construction companies in Jombang Regency to collect data for further analysis. Based on data analysis, four factors were obtained, namely human resource factors (X1), principles of Procurement of goods and services (X2), infrastructure condition factors and e-catalogue support system arrangements (X3), and benefits factors for implementing e-catalogues (X4). The results were then tested for validity and reliability to ensure the validity and reliability of the data. Further analysis was carried out using descriptive analysis methods and Pearson correlation analysis. The results of the descriptive analysis show that the highest factor in tenders for the Procurement of construction goods/services using the e-catalogue system is the human resources factor (X1), with a mean value of 3.620 and a standard deviation value of 0.047. According to the research outcomes regarding Pearson correlations the relationship between factors that has the highest correlation value is (X1) with (X3) both have a strong correlation with a correlation value of 0.771.